2016
DOI: 10.1016/j.carj.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Audit of Atypical Femoral Fractures and a Description of Some of Their Features

Abstract: Hospital discharge coding misclassified a great majority of femoral fractures as subtrochanteric. As an essential criteria for diagnosing AFF is their subtrochanteric location, this misclassification impaired our ability to retrospectively search for AFF patients. Radiologists tended not to report AFF when typical radiographic characteristics were present. Bilateral and multifocal disease is of interest in pointing to the diagnosis and in suggesting that the mechanism of injury in respect of these unusual frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
4
0
2
Order By: Relevance
“…However, it is the conjecture of the authors that some of these injuries were not recognised for what they were at the time of hospitalisation by orthopaedic surgeons or radiologists. This is the first study to our knowledge that has reported on whether or not AFF was diagnosed at the time of event by orthopaedic surgeon; however a previously published Canadian audit demonstrated that AFFs were not recognised by radiologists in all but one of 24 cases [14]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it is the conjecture of the authors that some of these injuries were not recognised for what they were at the time of hospitalisation by orthopaedic surgeons or radiologists. This is the first study to our knowledge that has reported on whether or not AFF was diagnosed at the time of event by orthopaedic surgeon; however a previously published Canadian audit demonstrated that AFFs were not recognised by radiologists in all but one of 24 cases [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Os bifosfonatos são o gold-standard no tratamento da osteoporose, com eficácia suportada pela evidência científica na prevenção das fraturas osteoporóticas. [1][2][3][4]7,[9][10][11] Desde 2005 têm surgido relatos de casos a sugerir uma relação entre o uso prolongado de bifosfonatos e a ocorrência de fraturas atípicas do fémur. 4-7,9,12 Figura 1.…”
Section: Comentáriounclassified
“…The ASBMR Task Force [6,7] summarized independent reports from 17 different countries. The wide difference of incidence reported from various sources has been attributed to differences in data collecting techniques with actual radiographic examination [15][16][17] generally finding a greater incidence than retrospective review of diagnostic codes. Some of these differences may also be attributable to observer bias, as the challenge of these fractures has occasioned intensely defensive reactions in some quarters.…”
Section: Establishing a Meaningful Definition Of Causationmentioning
confidence: 99%